2015
DOI: 10.1093/cid/civ344
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Hepatitis B Virus (HBV) DNA and Risk of HBV Reactivation in B-Cell Lymphoma: A Prospective Observational Study

Abstract: Monthly monitoring of HBV DNA is useful for preventing HBV reactivation-related hepatitis among B-NHL patients with resolved HBV infection following R-steroid-chemo (UMIN000001299).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
152
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(163 citation statements)
references
References 31 publications
8
152
3
Order By: Relevance
“…Reactivation of HBV in HBV surface antigen (HBsAg)-positive patients treated with immunosuppressive or cytotoxic chemotherapy is well known and has emerged as an important clinical issue [5][6][7]. In addition, although the risk is low, HBV reactivation in patients with resolved HBV infection-that is, in patients negative for HBsAg and positive for hepatitis B core antibody (HBcAb) and/or hepatitis B surface antibody (HBsAb)-also occurs [7][8][9][10]. It is well recognized that a low level of HBV persists in the liver and peripheral blood mononuclear cells in patients who have recovered from acute HBV infection [11,12]; subsequent immunosuppressive or cytotoxic chemotherapy may change the immune functions that control HBV replication and thus trigger HBV reactivation in these patients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reactivation of HBV in HBV surface antigen (HBsAg)-positive patients treated with immunosuppressive or cytotoxic chemotherapy is well known and has emerged as an important clinical issue [5][6][7]. In addition, although the risk is low, HBV reactivation in patients with resolved HBV infection-that is, in patients negative for HBsAg and positive for hepatitis B core antibody (HBcAb) and/or hepatitis B surface antibody (HBsAb)-also occurs [7][8][9][10]. It is well recognized that a low level of HBV persists in the liver and peripheral blood mononuclear cells in patients who have recovered from acute HBV infection [11,12]; subsequent immunosuppressive or cytotoxic chemotherapy may change the immune functions that control HBV replication and thus trigger HBV reactivation in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…It is well recognized that a low level of HBV persists in the liver and peripheral blood mononuclear cells in patients who have recovered from acute HBV infection [11,12]; subsequent immunosuppressive or cytotoxic chemotherapy may change the immune functions that control HBV replication and thus trigger HBV reactivation in these patients. The possible mechanisms involved have been discussed speculatively, but the precise clinical characteristics and virological features remain unclear, including the prevalence of HBV genotypes and of mutations known to be associated with HBV pathogenesis, such as A1762T, G1764A in the basal core promoter (BCP) region, G1896A in the precore (PC) region, and those in the S gene region [9,10,[13][14][15][16]. We studied the clinical and virological characteristics associated with HBV reactivation during or after immunosuppressive or cytotoxic chemotherapy in HBsAg-negative patients to clarify the pathogenesis of HBV reactivation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reactivation of HBV infection in HBsAg positive patients treated with immunosuppressive or cytotoxic treatment is well known (11)(12)(13). Reactivation in patients with resolved HBV infection (HBsAg negative, anti-HBc positive) can also occur during and after immunosuppressive or cytotoxic therapy.…”
Section: Hbv Reactivationmentioning
confidence: 99%
“…However, patients with lymphoma and with resolved HBV infection, HBV reactivation and severe HBV-related hepatitis were not fully prevented by "pre-emptive anti-HBV therapy" with entecavir (ETV). [5][6][7] Moreover, a randomized controlled study from Taiwan demonstrated a higher risk of HBV reactivation among the patients undergoing ETV as "pre-emptive therapy" compared to those who received this nucleoside analog as "prophylaxis" (18% vs. 2.4%, P=0.027).…”
mentioning
confidence: 99%